Comparison of Biochemical and Hematological Profile in Pulmonary and Extrapulmonary Tuberculosis at Gulab Devi Teaching Hospital - Kamal, Khadija; Shaheen, Aneela (Indus Journal of Bioscience Research, 2025)
Introduction: Tuberculosis (TB) remains a significant cause of morbidity among children in developing countries. Differentiating between pulmonary TB (PTB) and extrapulmonary TB (EPTB) based on laboratory parameters can aid in timely diagnosis and management. This study aimed to compare the biochemical and hematological profiles of pediatric patients diagnosed with PTB and EPTB at Gulab Devi Teaching Hospital. Methodology: This descriptive case series included 120 pediatric patients under 14 years of age diagnosed with TB over a three-month period. Patients were divided into PTB and EPTB groups. Biochemical and hematological parameters including Hb, RBCs, WBCs, TLC, PLT, ESR, CRP, and differential counts were analyzed. Radiological and clinical features such as TST positivity, chest X-ray findings, lymphadenopathy, cavity lesions, and miliary TB were also compared between groups. Data were analyzed using SPSS v25.0 with p ≤ 0.05 considered statistically significant. Results: Out of 120 patients, 74 (61.7%) had PTB and 46 (38.3%) had EPTB. Mean age was 7.01 ± 4.31 years, with a nearly equal gender distribution. PTB patients had significantly higher TLC (11.49 ± 1.95 vs. 8.30 ± 1.57; p=0.001) and WBC counts (11.10 ± 1.77 vs. 9.86 ± 1.58; p=0.001) compared to EPTB. Other hematological and biochemical parameters showed no significant differences. TST positivity was more frequent in EPTB (95.7% vs. 78.4%; p=0.010). Conclusion: While most biochemical and hematological markers were comparable between PTB and EPTB, significantly higher leukocyte counts in PTB suggest a more pronounced inflammatory response. Radiological findings and TST also differed notably, which can aid in clinical differentiation and early diagnosis.